1987
DOI: 10.1172/jci112928
|View full text |Cite
|
Sign up to set email alerts
|

In vivo regulation of human mononuclear leukocyte 3-hydroxy-3-methylglutaryl coenzyme A reductase. Studies in normal subjects.

Abstract: In vivo regulation of microsomal HMG CoA reductase activity was investigated in freshly isolated mononuclear leukocytes from 26 healthy adult males. Reductase activity exhibited a diurnal rhythm and decreased during fasting. Enzyme activity was also modulated in vivo by alterations in dietary and plasma cholesterol, suggesting the existence of an operative cholesterol feedback regulatory system. A single, high cholesterol meal decreased reductase activity within 2 h. In addition, rapid depletion of circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…In addition, urinary mevalonic acid has become an indicator of the effectiveness of statin drug treatment (Hiramatsu et al, 1998). However, our data are consistent with the data of Harwood et al (1987), indicating that the enzyme reaches its peak during the active feeding period of the animal, which in the case of rats would be during the dark period as opposed to the light period in humans. The presence of squalene epoxidase in cluster 4 further reinforces the validity of these observations.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, urinary mevalonic acid has become an indicator of the effectiveness of statin drug treatment (Hiramatsu et al, 1998). However, our data are consistent with the data of Harwood et al (1987), indicating that the enzyme reaches its peak during the active feeding period of the animal, which in the case of rats would be during the dark period as opposed to the light period in humans. The presence of squalene epoxidase in cluster 4 further reinforces the validity of these observations.…”
Section: Discussionsupporting
confidence: 92%
“…IV Regardless of the precise mechanism for suppression of HMG CoA reductase activity in FH, it is noteworthy that subjects with heterozygous FH and those with receptor-defective homozygous disease are able to show increased enzyme activity after rapid lowering of circulating cholesterol by plasmapheresis, whereas patients with LDL-receptor-negative homozygous FH exhibit little or no change in HMG CoA reductase activity after plasmapheresis. These results, and our previous studies (10), indicate that the effect of plasma exchange on mononuclear leukocyte HMG CoA reductase activity is due principally, if not entirely, to stimulation of the monocyte enzyme. The stimulation of HMG CoA reductase activity and, presumably, cholesterol biosynthesis, by plasmapheresis may provide insight into the rapid restoration of circulating cholesterol levels after this procedure in patients with FH (26-28).…”
Section: Introductionsupporting
confidence: 81%
“…Studies in healthy human subjects (10) indicate that mononuclear leukocyte HMG CoA reductase activity responds to various nutritional and pharmacologic perturbations in a manner similar to that of the enzyme isolated from animal intestine or liver (1 1). In the present investigation we measured the activity and protein content of HMG CoA reductase in mononuclear cells obtained from healthy adults and patients with heterozygous or homozygous FH.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in serum cholesterol concentration causes a compensatory induction of HMG-CoA reductase and, hence, mevalonate synthesis in extrahepatic cells (6). We have recently shown that mevalonate promotes the growth in mice of tumors derived from human breast cancer cells, probably through enhanced proliferation (7).…”
mentioning
confidence: 99%